STUDY OF JOKES AND THEIR TEXTUAL CHARACTERISTICS - Hikmatullo Haitboevich Dusmаtоv (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Anecdotes are one of the widespread artistic genres of Uzbek folklore, which has a centuries-old history, and has been alive and thriving for centuries. Therefore, researching the linguistic features of anecdotes based on the requirements of the times allows for a deep understanding of the linguistic features specific to all linguistic aspects of our national language. From this point of view, a wide study of various linguistic phenomena characteristic of our mother tongue, which is a huge and priceless wealth of our nation, including Uzbek anecdotes, which, although small in size, are very deep in content, and cover all aspects of society’s life, their expression in the speech process inculcating its possibilities in the minds of young people, introducing the peoples of the world to the linguistic features of comic-humorous texts in the Uzbek language is considered one of the urgent tasks of today. In this article, information about the study of anecdotes and their textual features is analyzed, and conclusions are made.